Cadmium-free buffer layer for electrochemically deposited chalcopyrite solar cell - Sun, Juan (2015)
The high efficiency CuInGaSe2 (CIGS) based thin film solar cells have been demonstrated by various groups across the globe. At present, the highest efficiencies are obtained using CdS buffer layers deposited by chemical bath deposition with a record efficiency of 20.9%. However, because of both environmental reasons and the fact that the CdS layer with a band gap of about 2.4-2.5 eV limits the transmittance of the short wavelength light into the absorber, development of a wide-band gap Cd-free buffer layer is currently the most pivotal topic in CIGS thin film PV technology. This thesis focuses on three parts: (i) to establish electrodeposited CuInSe2(CIS) as the absorber for the device fabrication, and (ii) to investigate the charge transport at absorber /buffer interface of the chemical bath deposited (CBD)-Zn(O,S) buffer layer, then last (iii) to develop low temperature solution based ZnSnO as alternative Cd-free buffer for CIS solar cells. Proof-of-concept devices of the electrodeposited CIS with these buffer layers yield power conversion efficiency (PCE) of ~4% for Zn(O,S)/CIS devices and 1.53% for ZnSnO/CIS devices. The first part of the thesis explores a solution based method to fabricate the CIS absorber. Electrodeposition was investigated for this purpose. Two deposition approaches (i) one-step electrodeposition and (ii) stacked elemental layer (SEL) deposition were compared. It was difficult for one step electrodeposition to achieve Cu-poor CIS as a post-selenization etching step using the toxic KCN is required. Moreover, the selenized CIS was porous with small grain size. On the other hand, SEL approach can easily control the Cu/In ratio by controlling the thickness of each layer. Selenization process, which is the most important for the SEL approach, was studied in details. And after a series of analysis and optimization, CIS with Cu/In ratio of 0.85 achieved 3.25% PCE with CdS buffer layer. The second part of the thesis focuses on the investigation of Zn(O,S) as a candidate of Cd-free buffer layer. As Zn(O,S) prepared by CBD method has a graded S/(S+O) composition, increasing the thickness of Zn(O,S) yields different composition profile. The optical and compositional properties of different thicknesses of Zn(O,S) were investigated. Next, the effect of thickness of Zn(O,S) on the buffer/absorber interface band alignment and charge relaxation was studied by XPS depth profiling and optical pump probe. It was found that the conduction band offset at the interface for different thicknesses Zn(O,S) /CIS was almost identical. Since the thinner Zn(O,S) has lower defect density, the thinner Zn(O,S)/CIS has much longer electron decay time than the thicker one. Both of these are the reasons why the Jsc and PCE of the 20nm Zn(O,S) is higher than the 50nm Zn(O,S) one. In addition, other solution based approach, such as spray pyrolysis was explored to control the S/(S+O) ratio inside the Zn(O, S) film. Lastly, ZnSnO was also explored as alternative Cd-free buffer layer for CIS solar cell. Two methods: (i) conventional and (ii) combustion sol gel methods were compared. Combustion method can generate high energy locally and this energy can help ZnSnO precursors to convert to ZnSnO semiconductor at relative low temperature and minimize the damage to the CIS absorber. The band gap of ZnSnO can be tuned by controlling the Sn concentration in the precursor and thus the band alignment between the ZnSnO and CIS. Promising device PCE of 1.35% was achieved by the ZnSnO/ CIS solar cell with 20%Sn.